Bond properties of alkali-activated slag concrete hollow block masonry with different mortar strength grades. (20th August 2019) - Jiao, Zhenzhen; Wang, Ying; Zheng, Wenzhong; Huang, Wenxuan; Zhao, Yujian
Highlights: Bond properties of alkali-activated slag concrete hollow block masonry are studied. Shear strength, flexural strength and axis tensile strength of masonry were tested. The effect of mortar strength grade on bond properties of masonry was evaluated. Higher mortar strength lead to higher bond strengths of masonry. Practical equations were developed to estimate mechanical properties of masonry. Abstract: The shear, flexural and axial tensile bond strengths of alkali-activated slag concrete hollow block (AASCHB) masonry layered with alkali-activated slag (AAS) mortar were investigated in this study. A comprehensive experimental investigation was conducted to assess the effect of the AAS mortar strength on the bond characteristics of the masonry. The bond strength of the AASCHB masonry was found to be directly related to the compressive strength of the AAS mortar, where higher compressive strength led to higher bond strength. In addition, new expressions for the bond strength were developed for AASCHB masonry based on the compressive strength of AAS mortar.